2022
DOI: 10.26434/chemrxiv-2022-kkcth
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trithiolato-Bridged Dinuclear Arene Ruthenium(ll)- Glycoconjugates: Synthesis and Antiparasitic Activity

Abstract: Eight novel carbohydrate-tethered trithiolato dinuclear ruthenium(II)-arene complexes were synthesized using CuAAC 'click' (Cu(I)-catalyzed azide-alkyne cycloaddition) reactions and, together with the diruthenium intermediates, were assessed for their in vitro activity against transgenic Toxoplasma gondii (T. gondii) tachyzoites constitutively expressing β-galactosidase (T. gondii β-gal), and for their cytotoxicity in non-infected host cells (human foreskin fibroblasts, HFFs). The results revealed that the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…VRE isolates were more susceptible to Ru-7 and Os-7 than MRSA isolates that aligns well with our previous observation ( Balázs et al, 2022 ). A very recent report showed that dinuclear Ru(II) sandwich complexes with O -acetyl protected galactopyranose moieties exhibited nanomolar IC 50 against Trypanosoma gondii , indicating a further potential field of application of the compounds presented here ( Holzer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 70%
“…VRE isolates were more susceptible to Ru-7 and Os-7 than MRSA isolates that aligns well with our previous observation ( Balázs et al, 2022 ). A very recent report showed that dinuclear Ru(II) sandwich complexes with O -acetyl protected galactopyranose moieties exhibited nanomolar IC 50 against Trypanosoma gondii , indicating a further potential field of application of the compounds presented here ( Holzer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 70%
“…In the quest for potential substitutes for platins, the half-sandwich type complexes of platinum-group metal ions (e.g., Ru(II), Os(II), Ir(III) and Rh(III)) have emerged as a promising compound class, with a large number of representatives displaying anticancer potencies [ 14 , 15 , 19 , 21 , 22 ]. In addition to the antineoplastic effects, several of these piano-stool complexes have different antimicrobial (e.g., antibacterial [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], antiparasitic [ 40 , 41 , 42 ], antiviral [ 30 , 43 ] and antifungal [ 44 ]) properties.…”
Section: Introductionmentioning
confidence: 99%